Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the product of [tex]\((y + 3)(y^2 - 3y + 9)\)[/tex], we will use the distributive property by multiplying each term in the binomial by each term in the trinomial. Here is a step-by-step solution:
1. Expand the terms:
We multiply [tex]\( y \)[/tex] by each term of [tex]\((y^2 - 3y + 9)\)[/tex]:
[tex]\[ y \cdot y^2 = y^3 \][/tex]
[tex]\[ y \cdot (-3y) = -3y^2 \][/tex]
[tex]\[ y \cdot 9 = 9y \][/tex]
2. Next, we multiply [tex]\( 3 \)[/tex] by each term of [tex]\((y^2 - 3y + 9)\)[/tex]:
[tex]\[ 3 \cdot y^2 = 3y^2 \][/tex]
[tex]\[ 3 \cdot (-3y) = -9y \][/tex]
[tex]\[ 3 \cdot 9 = 27 \][/tex]
3. Combine all the terms:
[tex]\[ y^3 + (-3y^2) + 9y + 3y^2 + (-9y) + 27 \][/tex]
4. Simplify by combining like terms:
- Combine [tex]\( -3y^2 \)[/tex] and [tex]\( 3y^2 \)[/tex]:
[tex]\[ -3y^2 + 3y^2 = 0y^2 = 0 \][/tex]
- Combine [tex]\( 9y \)[/tex] and [tex]\( -9y \)[/tex]:
[tex]\[ 9y - 9y = 0y = 0 \][/tex]
5. Write the resulting polynomial:
[tex]\[ y^3 + 0y^2 + 0y + 27 = y^3 + 27 \][/tex]
The correct product is:
[tex]\[ y^3 + 27 \][/tex]
Therefore, the answer is:
[tex]\[ \boxed{y^3 + 27} \][/tex]
1. Expand the terms:
We multiply [tex]\( y \)[/tex] by each term of [tex]\((y^2 - 3y + 9)\)[/tex]:
[tex]\[ y \cdot y^2 = y^3 \][/tex]
[tex]\[ y \cdot (-3y) = -3y^2 \][/tex]
[tex]\[ y \cdot 9 = 9y \][/tex]
2. Next, we multiply [tex]\( 3 \)[/tex] by each term of [tex]\((y^2 - 3y + 9)\)[/tex]:
[tex]\[ 3 \cdot y^2 = 3y^2 \][/tex]
[tex]\[ 3 \cdot (-3y) = -9y \][/tex]
[tex]\[ 3 \cdot 9 = 27 \][/tex]
3. Combine all the terms:
[tex]\[ y^3 + (-3y^2) + 9y + 3y^2 + (-9y) + 27 \][/tex]
4. Simplify by combining like terms:
- Combine [tex]\( -3y^2 \)[/tex] and [tex]\( 3y^2 \)[/tex]:
[tex]\[ -3y^2 + 3y^2 = 0y^2 = 0 \][/tex]
- Combine [tex]\( 9y \)[/tex] and [tex]\( -9y \)[/tex]:
[tex]\[ 9y - 9y = 0y = 0 \][/tex]
5. Write the resulting polynomial:
[tex]\[ y^3 + 0y^2 + 0y + 27 = y^3 + 27 \][/tex]
The correct product is:
[tex]\[ y^3 + 27 \][/tex]
Therefore, the answer is:
[tex]\[ \boxed{y^3 + 27} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.